2017
DOI: 10.1016/j.neulet.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

CaSR and calpain contribute to the ischemia reperfusion injury of spinal cord

Abstract: Spinal cord ischemia reperfusion injury (SCIRI) can cause spinal cord dysfunction and even devastating paraplegia. Calcium-sensing receptor (CaSR) and calpain are two calcium related molecules which have been reported to be involved in the ischemia reperfusion injury of cardiomyocytes and the subsequent apoptosis. Here, we studied the expression of CaSR and calpain in spinal cord neurons and tissues, followed by the further investigation of the role of CaSR/calpain axis in the cellular apoptosis process during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…At present, domestic and foreign studies have shown that one of the mechanisms of pathogenesis in SCIRI is the disturbance of calcium balance, including extracellular calcium influx, increase of calcium release from the ER and eventual intracellular calcium overload . Intracellular calcium homeostasis is primarily maintained by the ER and plays an important role in spinal cord injury after ischaemia/reperfusion .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, domestic and foreign studies have shown that one of the mechanisms of pathogenesis in SCIRI is the disturbance of calcium balance, including extracellular calcium influx, increase of calcium release from the ER and eventual intracellular calcium overload . Intracellular calcium homeostasis is primarily maintained by the ER and plays an important role in spinal cord injury after ischaemia/reperfusion .…”
Section: Discussionmentioning
confidence: 99%
“…At present, domestic and foreign studies have shown that one of the mechanisms of pathogenesis in SCIRI is the disturbance of calcium balance, including extracellular calcium influx, increase of calcium release from the ER and eventual intracellular calcium overload. 39,40 Intracellular calcium homeostasis is primarily maintained by the ER and plays an important role in spinal cord injury after ischaemia/reperfusion. 4 Mild tissue ischaemia/reperfusion can lead to ER dysfunction and induces the unfolded protein response of the ER, thereby relieving cellular stress and protecting cells from apoptosis or necrosis.…”
Section: Spinal Cord Ischaemia-reperfusion Injury Can Lead To Dysfuncmentioning
confidence: 99%
“…The influx of Ca +2 stimulates Ca +2 -dependent enzymes, within them are calpains, which seem to play a role in proteolysis by contributing to apoptosis in CNS cells. The cell death decreases mRNA expression and transcription of myelin basic protein (MBP) and proteolipid protein (PLP), which are axonal neurofilament proteins [49,51,52]. The administration of a calpain inhibitor such as E-64-d (1 mg/kg) to injured rats blocks apoptosis and helps to re-establish MBP and PLP genes [51].…”
Section: Treatment Outcomementioning
confidence: 99%